Inter-Regional Relations and the Asia-Europe Meeting (ASEM) (Palgrave Macmillan UK, 2018)
This edited volume examines contemporary relations between Europe and Asia through the prism of the Asia-Europe Meeting (ASEM). ASEM is an informal forum for dialogue and cooperation between 53 partners from both regions. Having started in 1996, ASEM aims to enhance political dialogue, strengthen economic cooperation, and promote socio-cultural exchange. The book provides insights into past achievements, current challenges, and possible new directions for ASEM as a dialogue forum. The chapters focus on institutional design, the security agenda, economic cooperation, and cultural exchange and civil society outreach through the Asia-Europe Foundation. They also zoom in on ASEM's Parliamentary Partnership, and the ongoing challenge of public awareness and visibility. Furthermore, they critically examine the implications of the widening process, the attempts to reinvigorate the forum, and the varied perspectives on ASEM's value for both regions. Appealing to policy-makers, researchers, and students, this volume provides an in-depth analysis of a wide range of issues relating to the role of ASEM in contemporary international relations. .